(untitled) (CIPEEX, 2025)
The objective of this literature review was to evaluate the knowledge of dental students regarding the correct indication of local anesthetics. For this, a search was conducted in the PubMed, Google Scholar, and CAPES Periodicals databases. Articles published between the years 2001 and 2024 were included in this review. The literature review showed that, in all analyzed articles, the students demonstrated unsatisfactory knowledge about the correct indication of local anesthetics, in addition to evidencing a lack of knowledge about vasoconstrictors.